Students' difficulties in understanding lecturer's explanation: a comparison between native and non-native lecturer - Ramita Ramita; Ratmanida Ratmanida (Journal of English Language Teaching, 2020)
This study is aimed to find out the students difficulty in understanding native and non-native lecturer which based on two aspects: linguistics and non-linguistics difficulties. It was also followed by the comparison of students difficulties in understanding both of lecturers.This study was conducted at English department students of Universitas Negeri Padang in academic year 2017/2018. The population of this research are all English education students in academic years 2017/2018 with the total number 95 students. Based on the population, the samples of this research are two classes: the first class are taught by native lecturer and second class are taught by non-native lecturer with the total number 64 students. This research used the descriptive collaborative method and used questionnaire as the main instrument followed by interview and observation to support the data from questionnaire. This research found that native lecturer tend to give more linguistics problem to the students rather than non-linguistics problem especially in lecturers accent and vocabulary understanding. Related to non-linguistics problem, lecturers speed placed the highest percentage. However, non-native lecture did not give significant difficulties but the higher percentage showed in non-linguistics problem especially in the way of lecturer in giving explanation.